INTERNET MEMES AS MODERN PHRASEOLOGICAL EXPRESSIONS - Sobirova Sevinch Sodik kizi; Safarova Durdona Davlatbek kizi; Bakhronboyeva Rukhshona Bakhtiyorovna; Ismoilova Sevinch Sunnat kizi; Ismoilova Mokhirakhon Ibrokhimjon kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This research explores internet memes as novel segments of phraseological expression in digital communication. This work analyzes memes in three popular meme constructions - I was today years old…, This is fine, and when you + clause structures, and describes their structural, semantic, and pragmatic aspects. Using qualitative linguistic investigation, the study shows how internet memes are semi-fixed, socially shared forms of language that encode meaning beyond literal interpretation. The results indicate that memes exhibit the key properties that characterize phraseological units in terms of stability, reproducibility, and idiomatic meaning. Also, the phrases contribute greatly to emotional expression, identity construction, as well as to the efficiency of communication in online discourse. Online memes are a new kind of digital phraseology which stems from multimodal communication and internet culture, according to the research.